Development and Characterization of Sodium Bicarbonate-Based Gel for Cytolytic Vaginosis - Carlos Gaspar; Ana Sofia Agonia; Sara Felício; Mariana Tomás; Diana Esteves; Rita Palmeira-de-Oliveira; Gilbert G. G. Donders; José Martinez-de-Oliveira; Ana Palmeira-de-Oliveira (Pharmaceutics)
Background/Objectives: Cytolytic vaginosis or, classically, Doderlein’s cytolysis is characterized by significant growth of species of the Lactobacillus genus, which leads to high amounts of lactic acid in the vaginal environment. Lactobacillus crispatus has been proposed as a key pathogen in this clinical condition. The symptomatology of cytolytic vaginosis is commonly confused with that of vulvovaginal candidosis, leading to inadequate and ineffective azole therapies. Nevertheless, historically, the use of sodium bicarbonate intimate baths was an effective way to reduce the symptoms of cytolytic vaginosis. Methods: In this study, four HPMC gel prototypes were developed, containing sodium bicarbonate concentrations ranging from 4% to 7% (w/w). These gels were evaluated for their physicochemical properties, antimicrobial activity, interference with lactobacilli adhering to cells, and cellular and tissue biocompatibility. Results: The gels presented pH values of around 9.0, and osmolality between 706 mOsm/kg (F4) and 1065 mOsm/kg (F7). The viscosity upon heating to physiologic temperature and dilution with simulated vaginal fluid was highly affected by the concentration of sodium bicarbonate. Gels with higher sodium bicarbonate concentrations (F6 and F7) were not shown to be stable in these conditions. All formulations exhibited effective antimicrobial activity against seven L. crispatus strains, with MIC values ranging from 6.25% to 25% (v/v) in terms of dilution. Additionally, the 4% (w/w) gel significantly interfered with the adhesion of L. crispatus to epithelial cells in competition and exclusion assays, reducing adhesion by more than 90% in relation to the control. Cytotoxicity tests on the Hec-1A, HeLa, and VK2/E6E7 cell lines indicated that the F4 and F5 gels demonstrated lower cytotoxicity levels compared to those with higher concentrations. Furthermore, ex vivo assays using porcine vaginal tissue confirmed that the 4% gel was non-toxic at a 25% (v/v) dilution. Conclusions: Based on these results, the 4% (w/w) sodium bicarbonate gel (F4) emerges as a promising therapeutic option for cytolytic vaginosis, offering effective bacterial interference, favourable physicochemical properties, and biocompatibility suitable for vaginal application.